Healthcare professionals’ perception of the World Health Organization Surgical Safety Checklist and psychological safety: a cross-sectional survey - Patricia Trbovich; Teodor Grantcharov; Susanne Rosthøj; Jeanett Strandbygaard; Kjestine Emilie Møller; Olivia Wisborg McLeskey (BMJ Open Quality)
Background The Surgical Safety Checklist (SSC) is a cornerstone of ensuring the safety and accuracy of communication among interdisciplinary teams in the operating room. Central to the successful implementation of such a checklist is the concept of psychological safety. Despite the extensive body of research on the checklists’ efficacy, the association between healthcare professionals’ (HCPs) perceptions of the checklist and their level of psychological safety remains uninvestigated. This study attempts to address this gap by examining how their perceptions of the checklist intersect with their sense of psychological safety.Methods A cross-sectional survey comprising 25 items was conducted from November 2022 to January 2023 on; Demographics (6 items), the SSC (12 items), and the Psychological Safety Scale (7 items). We invited 125 HCPs from five different professional groups in the operation ward to complete the survey.Results Of the 125 asked to participate, 107 responded, and 100 of whom completed the entire survey. The level of psychological safety increased by 1.25 (95 % CI 0.36 to 2.14, p=0.006) per one-point increase of the perception that colleagues listen when checklist items are being reviewed, and increased by 1.1 (95% CI 0.4 to 1.7, p=0.002) per one-point increase in the perception that the checklist enhances interdisciplinary teamwork, and increased by 0.86 (95% CI 0.15 to 1.57, p=0.02) per one-point increase in the perception that the checklist provides structure in the operating room. Conversely, the level of psychological safety decreased by 1.4 (95 % CI 0.5 to 2.3, p=0.004) per one-point increase in the perception that the checklist is time-consuming.Conclusion Our findings reveal a significant association between psychological safety levels and perceptions of the SSC. Increased psychological safety was linked to more positive views on the checklist’s role in enhancing interdisciplinary teamwork, creating structure and attentiveness among colleagues. While seeing the checklist as time-consuming was associated with a lower psychological safety rating. These results suggest that psychological safety influences how individuals view and engage with patient safety measures like the checklist, highlighting the importance of fostering a supportive environment to optimise safety practice.